OFDM MODULATOR IMPLEMENTATION IN FPGA FOR INDUSTRY 4.0 NETWORKS - Hernández, Fernando; Guillén Soriano, Camilo; González Ríos, Jorge Luis; Torres Gomez, Jorge (Telemática, 2022)
Industry 4.0 demands new paradigms in modern production factories worldwide, where the supporting communication infrastructure is critical. Higher transmission capacities with low-latency constraints are such key use cases for smart factories. Previous research outlines the feasibility of using orthogonal frequency division multiplexing (OFDM) modulation as a candidate in the next-generation industrial networks. The modeling and subsequent implementation of these mechanisms in FPGA facilitate the path toward future practical developments of functional communications systems. This paper investigates the hardware design in FPGA for transmissions and the modeling of the wired channel as a twisted copper pair cable using the System Generator simulator. The OFDM modulator is implemented, and the channel model follows the KHM parameters. The resulting simulation results evidence the feasibility of high-speed digital data transmission